Multi-responsive and multi-motion bimorph actuator based on super-aligned carbon nanotube sheets. (July 2019) - Li, Jingjing; Mou, Linlin; Zhang, Rui; Sun, Jinkun; Wang, Run; An, Baigang; Chen, Hong; Inoue, Kanzan; Ovalle-Robles, Raquel; Liu, Zunfeng
Abstract: Multi-responsive actuators have recently aroused intensive research for the requirements of being used in various environments. However, their actuation performances are generally lower than their single responsive counterparts because of the restriction of material selection and complicated structural design. Here, for the first time, a multi-responsive actuator that can respond to four types of stimuli including electricity, near infrared light, humidity, and organic vapors was designed by attaching superaligned carbon nanotubes sheets and coating an ink layer on the both sides of the PET film. The multi-responsive actuator shows fast and reversible actuation with high displacement-to-length ratio of 0.79 under electrical stimulus, and large bending angle of 212 ο in 0.55 s at a bending speed of 646 ο /s under near infrared light irradiation. The actuator also shows fast response exposing to moisture and volatile organic vapors. The actuator shows a large bending angle within ∼0.1 s when exposed to different organic solvents and recovered its initial shape when the solvent was removed. These performances are in the same level of the record values of the thermal-based bimorph actuators. We demonstrated this actuator as a smart electric-control frequency switch at relatively high on/off frequency up to 17.5 Hz. Graphical abstract: The IPS actuator exhibits fast multi-responsive behaviours and shows potential application in electrical-control frequency switch up to 17.5 Hz.Image 1